2016
DOI: 10.1089/thy.2015.0505
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Factors Influencing the Performance of Gene Expression Classifier Testing in Indeterminate Thyroid Nodules

Abstract: Nodule size did not affect GEC test performance in the present cohort. GEC benign results remain reliable in large nodules. GEC suspicious nodules >3 cm carry a similar risk of malignancy compared to smaller nodules, and do not warrant more aggressive treatment. GEC testing has limited clinical utility for HCNs due to the high rate of false-positive results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 34 publications
3
41
0
Order By: Relevance
“…Interestingly, the average malignancy rate of the surgical group of Bethesda IV (20.0%) was not higher than Bethesda III (24.5%) at our institution, consistent with published malignancy rates at other centres . Of note, the majority of malignancies from the FN/SFN category were follicular variant PTC, with few classic PTC cases as compared to the predominant PTC cases from the AUS/FLUS category.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Interestingly, the average malignancy rate of the surgical group of Bethesda IV (20.0%) was not higher than Bethesda III (24.5%) at our institution, consistent with published malignancy rates at other centres . Of note, the majority of malignancies from the FN/SFN category were follicular variant PTC, with few classic PTC cases as compared to the predominant PTC cases from the AUS/FLUS category.…”
Section: Discussionsupporting
confidence: 89%
“…Use of the Afirma GEC is recommended only for Bethesda III and IV categories to identify nodules that may not require surgical excision, with a reported 94%‐95% negative predictive value . Limitations to GEC testing include evaluation of Hurthle cell neoplasms (HCN), where many are categorized as Suspicious but resultant surgical resections contain few carcinomas; this limitation is currently a problematic area for clinicians . Our objective was to review the prevalence, malignancy rate and outcomes of patients with FNA specimens in the Bethesda cytology categories III and IV over a 5‐year period, including those with GEC Benign results.…”
Section: Introductionmentioning
confidence: 99%
“…[21] However, guideline does [21] There seems to be a growing consensus that BRAF V600E mutational status should be studied in association with other molecular and clinicopathological prognostic factors for a better risk stratification and this field is evolving. [22][23][24] The main limitation of our study was the modest numbers (n = 79) precluding us from making any firm recommendations. The results of our study with regards to the use of the novel RM8 antibody specific for the BRAF V600E mutations needs to be confirmed in a study with larger cohort of patients with PTCs.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, Lastra et al found that only 15% (2 of 13) of patients with a cytology suspicious for HCN and suspicious GEC harbored a malignancy 25. Wu et al also found an increased rate of “suspicious” GEC results in nodules with Hürthle cell predominance (77.4% vs 50.5% for nodules without Hürthle cell predominance, P <0.01), but there was no difference in the rate of malignancy (25.8% vs 25.3%) 26. Together, these data raise concern that there is an increased rate of suspicious GEC results in Hürthle cell lesions despite there being a relatively low risk of malignancy on surgical histology.…”
Section: Diagnosismentioning
confidence: 98%